Caracterização física, química e mineralógica dos solos em uma vertente do Parque Municipal das Mangabeiras - Quadrilátero Ferrífero (MG) - Adriane Nunes Pereira (2014)
The area known as “Quadrilátero Ferrífero” (or Iron Quadrangle, in English) has complex geological and geomorphic formations characterized by several vertex associated to poli-pedogenetic formations. Serra do Curral is located in the northern border of the Quadrangle, characterized by having relic areas from lateritic breastplates, more evident in the crest areas. However, in a low slope area, located within the Municipal Park of Mangabeiras, at the foot of this mountain chain, a cover with iron characteristics was found, which seems to be relic concretionary, the central point of this study. The material found was not neatly organized, with a lot of hull, presenting both weathered concretions and fragmented rocks, raising issues about its genesis. In this paper, the author seek answers for the issue raised, with the objective of characterizing the soils presented in the vertex studied, regarding its chemical, physical and mineralogical aspects, in order to understand how they have evolved, contributing towards the clarification of the genesis in the superficial formations in the study area, within the Quadrilátero Ferrífero. The methodology adopted included the organization of data in the preliminary characterization and collection stages, grain size analysis; mineralogical analysis, total chemical analysis; sulfuric acid; pH analysis and analyses of iron, aluminum and manganese extracted by the dithionite-citrate-sodium bicarbonate and ammonium oxalate. The results and discussions of the analyzed profiles allowed for the confirmation of the hypothesis raised, such as the formation of these slopes over colluvial material originating from a ferruginous crust that has possibly been formed in the crest parts of Serra do Curral, which might have descended to the bottom of the valley during its opening, forming soils that are even more weathered. This process is confirmed by both the crystallization of the iron through DCB and also the mineralogy and pH of the soil. The strong presence of hematite and magnetite, minerals present in the itabirite lithology, situated in the highest, crest parts, are also evidence of the colluvial deposition process in the genesis of these soils.